Activating mutations in EGFR and PI3K promote ATF4 induction for NSCLC cell survival during amino acid deprivation. Issue 4 (April 2023) - Takahashi, Mizuki; Okamoto, Yuka; Kato, Yu; Shirahama, Hitomi; Tsukahara, Satomi; Sugimoto, Yoshikazu; Tomida, Akihiro
Abstract: Some oncoproteins along with stress kinase general control non-derepressible 2 (GCN2) can ensure the induction of activating transcription factor 4 (ATF4) to counteract amino acid deprivation; however, little is known regarding the role of the oncogenic EGFR-PI3K pathway. In this study, we demonstrate that both mutated EGFR and PIK3CA contribute to ATF4 induction following GCN2 activation in NSCLC cells. The inhibition of EGFR or PI3K mutant proteins, pharmacologically or through genetic knockdown, inhibited ATF4 induction without affecting GCN2 activation. A downstream analysis revealed that the oncogenic EGFR-PI3K pathway may utilize mTOR-mediated translation control mechanisms for ATF4 induction. Furthermore, in NSCLC cells harboring co-mutations in EGFR and PIK3CA, the combined inhibition of these oncoproteins markedly suppressed ATF4 induction and the subsequent gene expression program as well as cell viability during amino acid deprivation. Our findings establish a role for the oncogenic EGFR-PI3K pathway in the adaptive stress response and provide a strategy to improve EGFR-targeted NSCLC therapy. Graphical abstract: Image 1